2013
DOI: 10.1097/aud.0b013e3182967534
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Real-Time Selection of Frequency Tables in an Acoustic Simulation of a Cochlear Implant

Abstract: Objectives Perception of spectrally degraded speech is particularly difficult when the signal is also distorted along the frequency axis. This might be particularly important for post-lingually deafened recipients of cochlear implants (CI), who must adapt to a signal where there may be a mismatch between the frequencies of an input signal and the characteristic frequencies of the neurons stimulated by the CI. However, there is a lack of tools that can be used to identify whether an individual has adapted fully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…Fusion of the sound information can take time, although how long is needed is undefined. There has been a suggestion that new mapping procedures and signal processing strategies are needed, for the second implant in bilateral implantation, to allow for better fusion between them [33][34][35]. Another potential for delay in the second side is that electrodes mapped to the same frequency range in each ear may stimulate different locations in each cochlea due to an insertion depth difference of each electrode array.…”
Section: The Second Side In Bilateral Cochlear Implantationmentioning
confidence: 99%
“…Fusion of the sound information can take time, although how long is needed is undefined. There has been a suggestion that new mapping procedures and signal processing strategies are needed, for the second implant in bilateral implantation, to allow for better fusion between them [33][34][35]. Another potential for delay in the second side is that electrodes mapped to the same frequency range in each ear may stimulate different locations in each cochlea due to an insertion depth difference of each electrode array.…”
Section: The Second Side In Bilateral Cochlear Implantationmentioning
confidence: 99%
“…The parameters for band partitioning were determined based on previous work on optimizing frequency band partitioning for a range of tasks (e.g., Shannon, 2004, 2005;Fitzgerald et al, 2013;Shannon, 1999b, 2002;McKay and Henshall, 2002;Shannon et al, 1998). The maps used in those studies (replotted in the Appendix) varied between either a logarithmic-like (Greenwood-like) partitioning or a purely linear partitioning.…”
Section: Analysis Filtersmentioning
confidence: 99%
“…In experiment 1, the synthesis filters were derived from the analysis filters by basally shifting all the frequencies by 0, 2, 4, and 6 mm relative to a 35-mm-long cochlea (Başkent and Shannon, 2005;Finley et al, 2008;Fitzgerald et al, 2013;Fu and Shannon, 1999b), as shown in panel 1 of Fig. 2.…”
Section: Synthesis Filtersmentioning
confidence: 99%
See 2 more Smart Citations